(untitled) (Architecture Image Studies, 2025)
Students’ reading abilities are very diverse because they are influenced by social, economic, and cultural factors. Diagnostic assessments are used to map students’ reading abilities and provide learning support that is appropriate to their level. This study aims to map students’ reading ability based on the results of literature analysis related to diagnostic assessment and explore how teachers facilitate students’ reading development based on the results of diagnostic assessment. This research is a type of literature study research. Data was collected through literature studies with the criteria of articles from Sinta indexed journals. The number of articles reviewed in this study is 5 articles with characteristics 1). Articles in the last 10 years, 2). The article reviewed is related to the focus of this research. Then the procedure for searching for articles needed in this study is based on the Google engine based on the analysis of learning strategies applied in each group of students. The results of this literature review show that from the results of the diagnostic assessment, students’ reading ability is divided into five levels, namely: (1) beginner level, (2) letter level, (3) word level, (4) paragraph level, and (5) story level. Then, from these five levels, the teacher facilitates the development of students’ reading by grouping students into three levels of learning, namely: (a) group 1 learning for beginner level and letters focusing on letter and sound recognition, (b) group 2 learning for word and paragraph levels practicing reading words and paragraphs intensively, and (c) group 3 learning for story level centered on understanding story texts. Therefore, based on the existing study, it can be concluded that the diagnostic assessment ensures that teachers apply appropriate learning, including letter and sound-based learning for beginner and letter-based groups, guided reading for word and paragraph groups, and discussion strategies to improve students’ understanding of stories for story groups.